2018
DOI: 10.1002/pro.3393
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of secretory abundant heat soluble protein 4 from one of the toughest “water bears” micro‐animals Ramazzottius Varieornatus

Abstract: Though anhydrobiotic tardigrades (micro‐animals also known as water bears) possess many genes of secretory abundant heat soluble (SAHS) proteins unique to Tardigrada, their functions are unknown. A previous crystallographic study revealed that a SAHS protein (RvSAHS1) from one of the toughest tardigrades, Ramazzottius varieornatus, has a β‐barrel architecture similar to fatty acid binding proteins (FABPs) and two putative ligand binding sites (LBS1 and LBS2) where fatty acids can bind. However, some SAHS prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…TDPs appear to be unique to tardigrades, with most possessing no sequence homology to non-tardigrade genes, proteins, or conserved domains [ 7 , 24 , 25 ]. There are a few exceptions, such as SAHS proteins which show low sequence homology to the Fatty Acid Binding Protein (FABP) family [ 32 , 33 ]. The low homology to FABPs seen for some SAHS proteins mirrors the lower predicted disorder for the SAHS family relative to other TDPs [ 7 ].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…TDPs appear to be unique to tardigrades, with most possessing no sequence homology to non-tardigrade genes, proteins, or conserved domains [ 7 , 24 , 25 ]. There are a few exceptions, such as SAHS proteins which show low sequence homology to the Fatty Acid Binding Protein (FABP) family [ 32 , 33 ]. The low homology to FABPs seen for some SAHS proteins mirrors the lower predicted disorder for the SAHS family relative to other TDPs [ 7 ].…”
Section: Main Textmentioning
confidence: 99%
“…A series of crystallographic studies on the SAHS proteins in Ramazzottius varieornatus have revealed the similarity between some SAHS proteins and a versatile class of proteins called fatty acid binding proteins (FABPs). The structures of Rv SAHS1 [ 33 ] and Rv SAHS4 [ 32 ] are similar to other canonical FABPs, characterized by an antiparallel β-barrel with an internal FA binding pocket, and a helix-turn-helix lid. In their 2017 study, Fukuda et al found that Rv SAHS1 binds to small fatty acids, but that bulky residues present in its two ligand binding sites (LBS1 and LBS2) prevent this protein from binding large membrane phospholipids.…”
Section: Main Textmentioning
confidence: 99%
“…While many tardigrade‐specific proteins with low or no sequence similarities to well‐characterized proteins are found, structural biology has revealed that some of their three‐dimensional structures are unexpectedly quite similar to those of known proteins. For example, secretory abundant heat soluble (SAHS) proteins are only found in some anhydrobiotic tardigrades, 27 but their structures are almost the same as those of fatty acid binding proteins (FABPs) and SAHS proteins can bind to fatty acids and other hydrophobic compounds as FABPs do 28,29 . We here showed that the TC2P is another example for “much different primary structure but the same tertiary structure.” More structural and functional analyses on tardigrade proteins may answer to why tardigrade proteins have evolved in such a unique way.…”
Section: Resultsmentioning
confidence: 75%
“…The main result of the study (result 1) shows that TDPs can protect E. coli BL21 under conditions of lyophilization [19,35] , allowing the storage of engineered strains at room temperature. A possible explanation for this effect was postulated in the waterreplacement hypothesis proposed by Thomas C. Boothby et al, according to which the TDPs are able to replace the hydrogen bonds formed between water and the cellular macromolecules.…”
Section: Discussionmentioning
confidence: 98%